Key determinants of organisational and technological innovation in UK SMEs: an empirical study. (2nd June 2008) - McAdam, Rodney; Reid, Renee; Harris, Richard; Mitchell, Neil
The aim of this paper is to conduct an empirical study of innovation incorporation in Small and Medium-sized Enterprises (SMEs) as a key sustainable source of competitive advantage, by controlling for key technological and organisational determinants. Large-scale changes in technology, markets and in large organisation strategies have resulted in the need for many SMEs to radically re-examine and modify their approaches to innovation management. This study uses a grounded SME innovation model, developed from earlier studies, as the basis of a questionnaire survey of 2086 SMEs in the UK. The results indicate that innovation was most strongly related to government grant aid, firm size, industrial sector, and the approach taken by the firm to organise how it develops products and processes.